The Effect of Ethanol Extract of Catâs Nettle Leaf (Acalypha indica Linn) to The Mortality of Aedes aegypti Larvae - Rizki, Yunika Varestri Anugrah; Sakiman, FX. Bambang Sukilarso; Mashuri, Yusuf Ari (Nexus Kedokteran Translasional, 2016)
Introduction: The incidency of Dengue Hemorrhagic Fever (DHF) in Indonesia is high. The best way of prevention is cutting the infection chains, one of them is using larvasida. Methanol extract of catâs nettle leaf is known as the killer of Aedes aegypti larvae in India. Here, the study is to examine if ethanol extract of catâs nettle leaf in Indonesia has same larvasida affect toward Aedes aegypti. It is because the catâs nettle leaf in Indonesia may have different variations. Methods: The study was a laboratoric experimental which was performed in Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, Central Java. The subject was catâs nettle leaf which was obtained from Sleman, Yogyakarta. Also, the indicator was 750 third instar Aedes aegypti larvas which were obtained from B2P2VRP Salatiga, Central Java. Ethanol extract of catâs nettle leaf was obtained from Pharmacology Laboratory of Gadjah Mada University. The study was a post test only control group design with 1 control group and 5 treatment groups. Each group was consisted of 25 larvae and was examined four times. Aquades of 100 ml was administered to the control group. While, the ethanol extract of catâs nettle leaf with concentration of 0,03%, 0,06%, 0,09%, 1,2% and 1,5% were administered to the treatment group. After 24 hours, observation and calculation of total larvae death were established. The data was analyzed by using Probit Regression and Curve Estimation. Results: The percentage of dead larvae in 0,03%, 0,06%, 0,09%, 1,2% and 1,5% of catâs nettle leafâs ethanol extract were 58%, 63%, 71%, 91% dan 94% respectively. The statistic result of Probit Regression shows that LC50 and LC99 are on 0,029% and 0,61% concentration respectively. Also, the Curve Estimation result shows that there is effect of ethanol extract of catâs nettle leaf to the mortality of Aedes aegypti larvae with tight correlation RÂ² = 0,888 and the linear regression equation is Y = 0,478 + 3,073 X. Conclusion: The ethanol extract of catâs nettle leaf induced effect to the mortality of Aedes aegypti larvae with LC50 on 0,029% concentration and LC99 on 0,61% concentration. Keywords: Aedes aegyptiÂ  larvae,Â  etanol extract of catâs nettle leaf,Â  LC50 and LC99